Innovation Practices of New Technology Adoption for the Business Survival Strategy of Online Travel Agencies During the COVID-19 Pandemic: Two Case Studies in Taiwan - Chu, Kuo-Ming (Journal of the knowledge economy, 2024)
The digital technologies introduced in recent years have transformed consumption practices, particularly in the tourism industry, which is currently struggling to survive during the coronavirus pandemic. The objective of this paper is to develop an academic structure to identify the impact of business innovation practices on performance and firm survival strategies, and to understand what new technologies are being used to mitigate the pandemic’s impact and to establish innovative practices that lead to sustainable business performance. Given the dynamic nature of the subject area, both quantitative and qualitative approaches have been adopted. Firstly, the paper employs a three-round Delphi survey with 15 senior executives of Taiwanese leisure tourism–related industries to develop measurement techniques. Secondly, based on the Delphi survey’s results, the study utilizes document analysis of website content and case documents of Asia’s leading online travel agencies (OTAs) during the pandemic. The results demonstrate that the business model of OTAs is to fill the gap in the free travel market with live-stream conferences that offer information quality and innovation practices that are more flexible, down-to-earth, and content marketing–oriented than traditional travel agencies. Furthermore, OTAs can strategically and financially ally themselves with suitable partners when facing major crises to strengthen their competitive advantage and create survival opportunities. Finally, AR/VR, AI, and big data (digital transformation) are integrated into daily operations to enhance service quality, close information gaps, increase the sense of travel security, and promote the decentralization of the travel industry. The research has practical implications for travel agency managers and policymakers, and the paper concludes by discussing challenges and future directions.